A Corpus-Based Analysis of Lexical Bundles in Korean Academic Discourse - 이혜경; 이선희 (담화와 인지, 2023)
This paper explores lexical bundles in Korean academic writings and formal conversations, with special attention to their possible usability in both L1 and L2 Korean learning. Drawing on the multi-morphemic sequences of Kang and Lee’s (under review) corpus-based study, the study provides a comprehensive overview of the usability of lexical bundles in four key areas: grammar patterns, register and genre, language acquisition, and pedagogy. By analyzing lexical bundles ranging from 3 to 6 grams, distinct usages are identified, particularly within content nouns, bound nouns, and final endings in Korean academic writings and formal conversations. Furthermore, the study examines dynamic discourse functions of Korean lexical bundles, focusing on stance, discourse organizing, and referential expressions. These findings align with prior research on English lexical bundles (Biber et al. 2004), providing valuable insights for understanding and characterizing academic discourse. With extensive uses as stance bundles in academic prose, the examination of selected bundles demonstrates versatile discourse functions utilizing the grammatical categories of particles and predicate endings in Korean. While the study elaborates on portions of the extracted lists, it acknowledges the need for further exploration and refinement of the entire lists.
Keywords: lexical bundles; formulaic expressions; multi-morphemic bundles; academic discourse; register